2009
DOI: 10.1007/s12576-009-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hyperexcitability of thalamic VPL neurons following unilateral spinal injury in rats

Abstract: In the present study, we have examined whether spinal hemisection injury induces changes in the electrophysiological properties of thalamic ventral posteriorlateral (VPL) neurons in rats. Male Sprague-Dawley rats were subjected to unilateral spinal cord injury by transverse hemisection at the T13 spinal segment. Four weeks after the T13 spinal hemisection, the injured rats displayed robust allodynic behaviors on both sides of hindpaws compared to sham controls (P < 0.05). Extracellular recordings taken 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…1,4 In addition, we and others have reported that hemisection results in bilateral hyperexcitability of the thalamic VPL neurons, whereas SNL produces hyperexcitability in the contralateral side of the thalamic VPL neurons. 12,13 The present study, combined with previous results, suggests that spinal hemisection produces bilateral neuropathic pain, whereas spinal nerve ligation produces unilateral neuropathic pain that runs through pathways including the spinal dorsal horn neurons, gracile neurons, and thalamic VPL neurons.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1,4 In addition, we and others have reported that hemisection results in bilateral hyperexcitability of the thalamic VPL neurons, whereas SNL produces hyperexcitability in the contralateral side of the thalamic VPL neurons. 12,13 The present study, combined with previous results, suggests that spinal hemisection produces bilateral neuropathic pain, whereas spinal nerve ligation produces unilateral neuropathic pain that runs through pathways including the spinal dorsal horn neurons, gracile neurons, and thalamic VPL neurons.…”
Section: Discussionsupporting
confidence: 79%
“…We and others have reported that hyperexcitability of the thalamic VPL neurons contributes to mechanical allodynia in the hindpaw, which includes similar mechanisms of neuropathic pain in the spinal dorsal horn. 12,13 In contrast to STTs, DC-MLs mediate non-noxious inputs to the supraspinal site of the gracile nucleus, and is considered an important ascending pathway for mechanical allodynia. However, the contribution of gracile neurons to the neuropathic pain seen with peripheral and spinal cord injuries remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The altered recognition of sensory input produces changes of distributional proportions after SCI. However, electrophysiological data suggest that WDR neurons do not lose their response properties to different sensory modalities; alterations in response to different sensory modalities produce an increase, rather than a decrease, in the proportion of WDR neurons in both the spinal dorsal horn and the thalamic VPL region after SCI [19,24]. However, the alterations of the electrophysiological response properties of dorsal horn neurons are not the only important factor contributing to neuronal hyperexcitability and proportional changes; neuroanatomical changes also are an important substrate in the spinal dorsal horn after SCI (see below).…”
Section: Hyperexcitability Of Spinal Dorsal Horn Neurons After Spinalmentioning
confidence: 99%
“…Thus, the reorganization of synaptic circuits contributes to hyperexcitability in both spinal and supraspinal regions after SCI. The hyperexcitability of VPL neurons suggests that supraspinal mechanisms also are important in contributing to CNP after SCI [19,20].…”
Section: Reorganization Of Synaptic Circuits In Spinal Dorsal Horn Afmentioning
confidence: 99%
“…Such changes have been implicated in the induction and maintenance of SCI pain. Identification of molecular mechanisms underlying this "gliopathy" [29,31,32] may therefore help to clarify the pathobiology of SCI pain and lead to the elucidation of novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%